All-cause mortality among Japanese-Brazilians according to nutritional characteristics Mortalidade por todas as causas entre nipo-brasileiros de acordo com as características nutricionais - Flavia Cincotto Massimino; Suely Godoy Agostinho Gimeno; Sandra Roberta Gouveia Ferreira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
The aim of this study was to verify the association between nutritional variables and mortality in a Japanese-Brazilian cohort. In 1993, 647 subjects were interviewed with food frequency questionnaires and scheduled for physical procedures (weight, height, blood pressure) and biochemical tests (oral glucose tolerance test). Student's t test was used to compare the mean values of target variables between living and deceased subjects. Mortality rate and hazard ratios were obtained (crude and adjusted) according to the nutritional variables. Overall mortality rates were 21.4 and 11.7/1,000 person-years for males and females, respectively. Smoking, diabetes, sedentary lifestyle, hypertension, higher mean age, high blood pressure, high blood glucose, and higher percent weight gain and rate of weight gain were observed in the history of deceased subjects. After adjusting for control variables, an increase was observed in mortality among individuals with lower carbohydrate and cholesterol intake. The results suggest that mortality risk factors like age, chronic diseases, sedentary lifestyle, smoking, and inadequate diet must also be acting in the Japanese-Brazilian population. O objetivo do estudo foi verificar a existência de associações entre variáveis nutricionais e a mortalidade em uma coorte de nipo-brasileiros. Em 1993, 647 indivíduos foram entrevistados (questionário de freqüên- cia alimentar), submetidos ao exame físico (peso, altura, pressão arterial) e a exames bioquímicos (teste de tolerância oral à glicose). O teste t de Student foi utilizado para comparar valores médios das variáveis de interesse entre vivos e mortos. Obtiveram-se as taxas de mortalidade e razões entre esses coeficientes (brutas e ajustadas) segundo variáveis nutricionais. Observou-se taxa de mortalidade geral de 21,4 e 11,7/mil pessoas-ano para homens e mulheres, respectivamente. Entre os indivíduos que morreram, encontrou-se maior porcentagem de sujeitos diabéticos, sedentários e hipertensos. Após ajuste às variáveis de controle, observou-se maior mortalidade entre os com menor consumo de glícides e colesterol. Conclui-se que os fatores de risco clássicos para mortalidade, como idade, doenças crônicas, sedentarismo, tabagismo e dieta, devem estar atuantes também na população nipo-brasileira.